2016
DOI: 10.1155/2016/1813979
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tai Chi Chuan on Improving Mind‐Body Health for Knee Osteoarthritis Patients: A Systematic Review and Meta‐Analysis

Abstract: Purpose. To conduct a meta-analysis and systematic review examining whether Tai Chi Chuan could have mental and physical benefits for patients with knee osteoarthritis. Methods. MEDLINE, PUBMED, EMBASE, and CINAHL databases were searched for relevant studies. Data of the studies were collected, and outcomes were classified using the International Classification of Functioning, Disability, and Health model. Effect sizes of the mental and physical components were determined, along with the recommendation grades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
0
36
0
4
Order By: Relevance
“…Another study found that Tai Chi exercise increases varicella-zoster virus specific cell-mediated immunity [ 16 ]. In addition, Chang et al reported that the evidence-based results of Tai Chi exercise had small-to-moderate effects on body functions and structures, activities, and participation of physical component [ 17 ]. It is of note that our findings that Tai Chi synergy T1 exercise increased CD19+ B cells and CD16+CD56+ NK/T cells but decreased CD16-CD56- cytotoxic T cells are consistent with all the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that Tai Chi exercise increases varicella-zoster virus specific cell-mediated immunity [ 16 ]. In addition, Chang et al reported that the evidence-based results of Tai Chi exercise had small-to-moderate effects on body functions and structures, activities, and participation of physical component [ 17 ]. It is of note that our findings that Tai Chi synergy T1 exercise increased CD19+ B cells and CD16+CD56+ NK/T cells but decreased CD16-CD56- cytotoxic T cells are consistent with all the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Qigong exercises can reduce pain, improve functional abilities (postural stability, muscular strength, flexibility) and help KOA patients maintain normal life activities (18)(19)(20)(21)(22). Baduanjin Qigong (BD), one of traditional Chinese Qigong exercise (Tai Chi, Wuqinxi, and Liuzijue) therapies (23,24), has a great emphasis on mind-body integration; slow body movements along with musculoskeletal stretching should be coordinated with deep breathing, physical relaxation, and mental concentration, leading to a deep state of meditative therapy (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…17 Specific therapies such as yoga, Tai Chi, balance training, and aquatic exercise have shown some minor improvement in symptoms related to knee OA. [18][19][20][21][22] Weightbearing strength training, non-weightbearing strength training, and aerobic exercise have all been shown to be effective for short-term pain relief in knee OA, with non-weight-bearing strength training being the most effective. 23 Strengthening of the upper leg muscles is thought to be one of the factors involved in reducing pain associated with knee OA.…”
Section: Weight Management Can Slow Progression Of the Diseasementioning
confidence: 99%